Kunst um 1970 Art Around 1970 : Sammlung Ludwig Aachen im Künstlerhaus Wien. - Ludwig, Peter; Becker, Wolfgang (Wien : Künstlerhaus Wien, 1977)
Aeppli, Eva ; Alvermann, Hans-Peter ; De Andrea, John ; Bailey, William ; Baselitz, Georg ; Becher, Bernd & Hilla ; Botero, Fernando ; Brecht, Georg ; Christensen, Dan ; Christo ; Close, Chuck ; Cottingham, Robert ; Darboven, Hanne ; Eddy, Don ; Erro ; Estes, richard ; Gertsch, Franz ; etc.
Kunst um 1970 Art Around 1970 : Sammlung Ludwig Aachen im Künstlerhaus Wien, März 8 bis Juni 12, 1977
Duits
kunstcatalogus